STRATEGI DOWNWARD COMMUNICATION PIMPINAN DALAM MENINGKATKAN PERFORMANCE PEGAWAI di SETDAKAB ACEH SELATAN - Junaidi, Jubir; Maulida, Desi (Universitas Teuku Umar, 2024)
As an effort to improve the work performance of employees, of course the role of leadership is needed in providing direction/instructions, motivation and also all forms that can improve employee performance. This phenomenon is what causes the importance of this research. The aim of this research is to find out how the downward communication strategy used by the leadership improves the performance of employees in the South Aceh Regional Secretariat and what are the obstacles to the downward communication strategy. The method used in this research is descriptive qualitative and uses purposive sampling techniques by obtaining data from interviews, field observations and documentation studies. The informant in this research was the Head of Protocol and Leadership Communications as the key informant, then the additional informants were one person from the Head of Subdivision and two employees. The data analysis technique uses the concluding drawing verification technique, by drawing conclusions that can answer the problem of the topic being studied. The results of the research show that the downward communication strategy carried out by the leadership is optimal, this is characterized by providing clear directions to employees, then providing motivation to provide excellent work enthusiasm to employees, providing information regarding working hours that is transparent. which makes employees organized and disciplined, the feedback provided by the leadership which makes employees more innovative in their work is good and the provision of information about ideology which makes employees more confident and integrated is also very good.